2013
DOI: 10.15517/rbt.v61i2.11232
|View full text |Cite
|
Sign up to set email alerts
|

The role of microhabitat in predation on females with alternative dorsal patterns in a small Costa Rican anole (Squamata: Dactyloidae)

Abstract: Papel del microhábitat en la depredación de hembras con patrones dorsales alternativos en una pequeña lagartija de Costa Rica (Squamata: Dactyloidae). Predation is one of the major selective agents influencing evolution of color patterns. Cryptic color patterns decrease detection probability by predators, but their concealing function depends on the background against which patterns are seen; therefore, habitat use and color patterns are tightly linked. in many anole species, females exhibit variation in dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Models of the lizard Norops ( Anolis ) humilis (Polychrotidae) representing females with different natural back patterns were differentially attacked in different microhabitats, supporting a role for predation in maintaining polymorphism in this species (Paemelaere, Guyer & Stephen Dobson, ). By contrast, studies using clay models have also revealed no significant difference in attack frequency for polymorphisms in other species, suggesting that the morphs have no defensive role.…”
Section: The Questionsmentioning
confidence: 99%
“…Models of the lizard Norops ( Anolis ) humilis (Polychrotidae) representing females with different natural back patterns were differentially attacked in different microhabitats, supporting a role for predation in maintaining polymorphism in this species (Paemelaere, Guyer & Stephen Dobson, ). By contrast, studies using clay models have also revealed no significant difference in attack frequency for polymorphisms in other species, suggesting that the morphs have no defensive role.…”
Section: The Questionsmentioning
confidence: 99%
“…Future studies of A. fuscoauratus will benefit from characterizing dewlap color spectra, identifying key predators, and quantifying differences in predation intensity among dewlap color phenotypes and localities, for instance, using clay models (Steffen 2009; Paemelaere et al. 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Females lay a single egg in leaf litter as often as every seven days with the greatest activity during the rainy season (Guyer and Donnelly, 2005, apparently erroneously stated that reproductive activity peaks during the dry season). Paemelaere et al (2011Paemelaere et al ( , 2013) studied dorsal pattern morphology and microhabitat selection in female N. quaggulus at La Selva, Costa Rica, in relation to their survival rates.…”
Section: Undisturbed Vegetation'' (Mccranie Andmentioning
confidence: 99%